Can visitors visually distinguish successive coastal landscapes? A case study from the Curonian Spit (Lithuania). (January 2016) - Povilanskas, Ramūnas; Baziukė, Dalia; Dučinskas, Kęstutis; Urbis, Arvydas
Abstract: Visual distinctiveness of the series of successive coastal landscapes featuring the Curonian Spit, a UNESCO World Heritage site, has been investigated using black and white landscape photos as visual stimuli. Based on the results of the chi-square test it was confirmed with strong statistical evidence that lay visitors indeed are capable of visual distinguishing different coastal landscapes and habitats which occur in the succession series from the shifting dunes to the mature forest. In all investigated 45 different cases of coastal landscapes the 'null hypothesis' was rejected with p  < 0.00001. If the photographs representing the landscapes are carefully selected by a dedicated group of professionals, then lay visitors can correctly distinguish the landscapes and/or habitats even in the case when black and white photographs are applied as visual stimuli. Highlights: Based on the results of the chi-square test it was confirmed with strong statistical evidence that lay visitors indeed are capable of visual distinguishing different coastal landscapes and habitats. In all investigated 45 different cases of coastal landscapes the 'null hypothesis' was rejected with p  < 0.00001. Lay visitors can correctly distinguish the landscapes and/or habitats even in the case when black and white photographs are applied as visual stimuli.